2014
DOI: 10.1021/ja411855d
|View full text |Cite
|
Sign up to set email alerts
|

NiXantphos: A Deprotonatable Ligand for Room-Temperature Palladium-Catalyzed Cross-Couplings of Aryl Chlorides

Abstract: Although the past 15 years have witnessed the development of sterically bulky and electron-rich alkylphosphine ligands for palladium-catalyzed cross-couplings with aryl chlorides, examples of palladium catalysts based on either triarylphosphine or bidentate phosphine ligands for efficient room temperature cross-coupling reactions with unactivated aryl chlorides are rare. Herein we report a palladium catalyst based on NiXantphos, a deprotonatable chelating aryldiphosphine ligand, to oxidatively add unactivated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 147 publications
(98 citation statements)
references
References 130 publications
(78 reference statements)
2
96
0
Order By: Relevance
“…26 LiN(SiMe 3 ) 2 was found to be an effective base because it can generate benzyllithium intermediates by deprotonation of benzylic protons activated by η 6 -coordination of the arene to Cr(CO) 3 . After Pd-catalyzed coupling of this deprotonated species, the resulting triarylmethane−Cr(CO) 3 complex was decomposed by exposure to air and light to give the triarylmethane in excellent yield.…”
Section: Acs Catalysismentioning
confidence: 99%
“…26 LiN(SiMe 3 ) 2 was found to be an effective base because it can generate benzyllithium intermediates by deprotonation of benzylic protons activated by η 6 -coordination of the arene to Cr(CO) 3 . After Pd-catalyzed coupling of this deprotonated species, the resulting triarylmethane−Cr(CO) 3 complex was decomposed by exposure to air and light to give the triarylmethane in excellent yield.…”
Section: Acs Catalysismentioning
confidence: 99%
“…This value is significant given that a small difference of 0.08 was found for natural charges on phosphine atoms between trialkyl phosphine and triphenyl phosphine using the the same computational method. 55 To test our hypothesis of stronger C−F → Ln/An interactions, the homoleptic model complex Ce[N(SiMe 3 )-(C 6 H 4 F)] 3 (1-F 1 ) was synthesized and compared to previously reported Ce[N(SiMe 3 )(C 6 F 5 )] 3 (1-F 5 ). 32 Stirring an n-pentane solution of Ce[N(SiMe 3 ) 2 ] 3 with HN(SiMe 3 )(C 6 H 4 F) led to a white precipitate of 1-F 1 during 6 d in 68% yield.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that under the basic reaction conditions, NiXantphos is likely deprotonated, leading to a very electronrich palladium center. 21 Additionally, van Leeuwen and coworkers disclosed that NiXantphos has both a larger bite angle and is more flexible than Xantphos. 22 Investigations are ongoing in our lab to try to ascertain which of these phenomena, if either, leads to the observed difference in reactivity.…”
Section: Figure 2 Pka Trends Of Transmetalation Reagents In Cross-comentioning
confidence: 99%